(untitled) (Revista Contexto & Saúde, 2026)
Aim: To analyze how food and nutritional surveillance (FNS) is incorporated into the care of overweight and obese individuals within Primary Health Care (PHC) in Mato Grosso do Sul (MS), based on the perspective of health professionals. Methods: Cross-sectional, quantitative study with PHC professionals in MS using an online questionnaire about the role of health teams in caring for overweight and obesity. The professionals were categorized into: 1) reference to FNS practice, and; 2) Do not consult FNS practice. The chi-square test and linear regression were performed to analyze the difference between the two groups (5% significance). Results: Regarding the treatment of overweight and obesity, differences were observed for: Nutritional Care, Early Diagnosis, Promotion of Physical Activity and Medication Treatment. Note that when the team performed FNS, the chance of offering PICs increased (OR= 3.78; 95% CI 1.48 – 9.60), knowledge of referral flows for specialized care (OR=2.99 ;95%CI 1.21–7.38), carrying out an assessment of food consumption (OR=3.72; 95%CI 1.48–9.32) and the unit offering individual care for overweight patients. and obesity (OR=3.70; 95%CI 1.12–12.23). Conclusion: The FNS has a positive effect on the care of overweight and obesity in PHC in Mato Grosso do Sul.